Ki Hajar Dewantara's Philosophy in its Application in Senior High School Economic Learning - Musfidah, Heny; Nursalim, Mochamad; Masitoh, Siti (Continuous Education: Journal of Science and Research, 2023)
This journal article aims to discuss the various philosophies of Ki Hajar Dewantara. It is hoped that this can be a means of analysis to conclude which philosophies or thoughts are the basis for implementing the Independent Learning Curriculum in high school economics learning. This research uses a literature study method in the form of various materials in the form of articles, notes and various related journals. In this case, the teacher has the freedom to: (1) determine learning activities and learning tools in accordance with the learning objectives, the context of the educational unit, and the characteristics of the students and (2) determine the type, technique, form of instrument, and timing of the assessment based on the characteristics of the learning objectives.